Diseño de tubería de revestimiento y cementación de un pozo en el oriente ecuatoriano - Peñafiel A, Pedro (2009)
This document aims to show clearly and organized an alternative for the design of casing and current cementing of an oil well of eastern Ecuador, and the improvement of quality in technical services and drilling operations in the oil industry. The first part is a summary of the drilling program conducted in this well. Later comes a summary of the most important basic procedures which are explained easily and neatly, establishing a design methodology that identifies the minimum loads to be considered, factors and design loads minimum established by the API (explosion, collapse and tension), applying the method of trial and error. In addition, presents the costs for such process. In the second part of the document presents the process of cementing the well and the calculations to determine the volumes and number of bags corresponding to optimize the process technically and economically. It also presents the costs for that activity. It is very important to note that this type of procedure is under constant evaluation and that these may vary due to causes or supported studies involving process optimization.